Wajah Spanduk Solidaritas Gempa Yogyakarta: Tinjauan dari Perspektif Komunikasi - - Isbandiyah HS. (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2008)
This paper is based on case study on the use of banner as a medium to communicate human solidarity to the victims of Yogyakarta earthquake on May 2006 as part of public information campaign. This paper shows that banners are effective ways to inform, persuade people to have a good feeling and spirit of life.